Exploring the Relationship between Consumer Price Index (CPI) and Producer Price Index (PPI) in Nigeria - Oyeleke, Olusola Joel; Ojediran, Oladele Adeyi (Advances in Social Sciences Research Journal, 2018)
The study investigated the relationship between consumer price index (CPI) and producer price index (PPI) in Nigerian economy, using monthly data from 2013: 01 to 2018: 05. The study employed DF-GLS unit root test to verify the stationarity of the series. Cointegration tests involving Johansen and Engle-Granger approaches could not detect long run relationship between CPI and PPI, implying that the variables could not be substituted for each other in measuring inflation rate in Nigeria. Vector Autoregressive (VAR) technique was used to analyse the variables and the results revealed that there was no causality between CPI and PPI in Nigeria. However, the OLS result in Engle-Granger 2-step approach to cointegration provided a useful insight into the relationship between the variables. An increase in either CPI or PPI exerted a statistically significant reduction effect on the rate of other in the long run.